Ziswaf Fundraising and Distribution Strategy during Covid -19 Pandemic at Laziswaf Unida - Damar Jamil (NUsantara Islamic Economic Journal, 2023)
In March 2020, the world was shaken by an outbreak of the corona virus, the virus first appeared in the Chinese city of Wuhan. Almost all countries are affected by it, including Indonesia. The impact caused by the corona virus is multidimensional social, economic, political, educational, and health. For example in the economic sector, with the issuance of instructions from the government, the lockdown of all economic activities has stopped, and if it continues it will cause a crisis in this field, for zakat institutions this corona virus has an impact on zakat collection. Therefore zakat institutions must innovate in dealing with this pandemic, which indirectly becomes a moment to educate the wider community about the importance of zakat and the effects of it, so as to grow in each of them a culture of sharing and caring for those around them. The purpose of this study is to find out and analyze the right strategy for collecting zakat and distributing it in the wider community, reflecting on what is in the Islamic boarding school environment which has been able to have a significant impact even in a pandemic situation, especially if it is applied to the wider community. The approach used in this paper is descriptive qualitative. The main data source for this paper is information obtained from interviews and observations from the executors of these activities in the hut itself. The conclusion of this paper is that the strategy in implementing zakat activities is very important to support its success. As a whole, we are currently still integrating manual and digital collections. Both of these strategies are still the mainstay.